2012
DOI: 10.1007/s10072-012-0978-0
|View full text |Cite
|
Sign up to set email alerts
|

Propofol exerts hippocampal neuron protective effects via up-regulation of metallothionein-3

Abstract: Propofol is an intravenous anesthetic with neuroprotective effects against cerebral ischemia or hypoxia injury. However, the underlying mechanisms remain obscure. Recent years emerging evidence has demonstrated that metallothionein-3 (MT-3), a growth inhibitory factor that exists mainly in the central nervous system, exhibited neuroprotective effect in vivo. Here, we used a model of hypoxia/re-oxygenation (H/R) injury to examine the hippocampal neuroprotective effect of propofol, and explored the role of MT-3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 28 publications
1
5
0
1
Order By: Relevance
“…Recently, a growing number of evidences have demonstrated that propofol improved learning and spatial memory functions [11,12], indicating that hippocampus is one of the target structures of propofol in brain. This has been further confirmed by in vivo studies showing that propofol was able to attenuate hippocampal neuron death and promote neurogenesis after oxygen deprivation or cerebral ischemia [4,13]. Consistent with these findings, the present study, revealed a significant increase in hippocampal neuron cell survival during H/R after pretreatment with 50 μM propofol.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, a growing number of evidences have demonstrated that propofol improved learning and spatial memory functions [11,12], indicating that hippocampus is one of the target structures of propofol in brain. This has been further confirmed by in vivo studies showing that propofol was able to attenuate hippocampal neuron death and promote neurogenesis after oxygen deprivation or cerebral ischemia [4,13]. Consistent with these findings, the present study, revealed a significant increase in hippocampal neuron cell survival during H/R after pretreatment with 50 μM propofol.…”
Section: Discussionsupporting
confidence: 91%
“…Propofol may also exert neuroprotective effects following oxygen deprivation, cerebral ischemia, and traumatic brain injury. Animal studies demonstrate that propofol significantly reduces hypoxia‐mediated increases in lactate dehydrogenase, decreases morphological signs of cell damage, and increases neurogenesis . The reduction in ED, as described, may also be exerted through a neuroprotective effect .…”
Section: Pharmacologymentioning
confidence: 66%
“…1c, d). 208 Then, we focused on the protective property of propofol, 209 and observed that the Ang II-induced apoptosis was (He et al, 2013). Consistently, we observed that Ang II (p < 0.01, n = 5), which was reversed by propofol pre- (by about 52.1 ± 3.6%, p < 0.01, n = 5) and cIAP-1 292 (by about 62.2 ± 3.4%, p < 0.01, n = 5) (Fig.…”
mentioning
confidence: 99%